The Making of Local Microorganisms (LMO) Liquid Fertilizer from Banana Corm in Talang Mulya Village, Pesawaran Regency, Lampung Province - Muzakki, Khairul Umam; Khova, Muhammad Fathurrahman; Fadhila, Zalfa; Putri, Khatarina Septi Amelia; Putra, Tri Ramanda; Anatasya, Anatasya; Kinanti, Regita Tiara Sekar; Sutawa, Wira Adiguna (Research and Social Study Institute, 2023)
Local microorganisms (LMO) liquid fertilizer made from banana corm is an alternative fertilizer that is considered more affordable and safe because it utilizes natural substances that are easy to obtain. This article was written based on the community services activity that had been conducted in Talang Mulya Village Hall, Teluk Pandan Subdistrict, Pesawaran Regency, Lampung Province. This activity aimed to provide an overview of the program implementation in making LMO liquid fertilizer from banana tree corm, comprising the making practice and material presentation. The method used was a qualitative approach with a descriptive-explanatory model. This activity was carried out through socialization by targeting farmers as the participants. The results show that the community of Talang Mulya Village, especially those who work as farmers, has acquired new understanding and insights regarding natural substances-based liquid fertilizer that has the ability to fertilize the agricultural land. Through implementation of this community services activity, the village community can make their own liquid fertilizer from natural substances so that they can reduce their expenses amidst the cultivation process of their agricultural plants. After the implementation of this activity, the farmers can easily make liquid fertilizer to be applied directly to their cultivated plants.